Design and implementation of an integrated accounting architecture for distributed UMTS and WLAN networks. (21st January 2008) - Racz, Peter; Forster, Volker; Stiller, Burkhard
Accounting for resource and service usage in communication networks forms the basis of network operators' business, and is therefore essential. Within a heterogeneous, multidomain mobile environment of emerging new access technologies, the demand for a distributed accounting infrastructure becomes more relevant. Driven by the analysis of current accounting solutions in Universal Mobile Telecommunications System (UMTS) and Wireless Local Area Networks (WLAN) networks, the newly developed approach presents an integrated accounting architecture based on the Diameter protocol, forming a flexible basis for charging UMTS and WLAN communication services. The system developed is described, discussed and evaluated by a prototypical implementation.